Longer Duration of SARS-CoV-2 Infection in a Case of Mild COVID-19 With Weak Production of the Specific IgM and IgG Antibodies - Guo, Xuemin; Zeng, Lizhu; Huang, Zhen; He, Yongjun; Zhang, Zhuojin; Zhong, Zhixiong (Frontiers in Immunology, 2020)
Background: The relationship between SARS-CoV-2-carrying time and specific antibody production has not been reported yet in re-admitted COVID-19 patients. We reported a case of mild COVID-19 with long virus-carrying time, weak production of virus-specific IgG and IgM antibodies, and recurrence of positive SARS-CoV-2 RNA in stool specimens after discharge. Case presentation: A 27-year-old male was diagnosed as COVID-19 after returning to Meizhou from Wuhan. Despite of extremely mild symptoms, the patient was hospitalized for 24 days because of persistently positive SARS-CoV-2 RNA detection. Three days after recovery discharge, he was hospitalized again for 7 days due to recurrence of the positive SARS-CoV-2 RNA result, while in a good physical condition. Serological assay by using a fluorescent immunochromatography detection kit specific to SARS-CoV-2 showed that SARS-CoV-2-specific IgM were under detectable and IgG were very low on day 8 after onset; both of them seemingly reached a top concentrations on day 15 (just 6-fold increase of the IgG titer), and then decreased, remaining relatively stable from day 25 after onset to discharge. The production of the IgM and IgG targeting SARS-CoV-2 in this very mild case was much lower than that in a severe case of COVID-19 at the same hospitalizing period, the later which was used as a control. Conclusion: Mild COVID-19 patients could carry SARS-CoV-2 for a long time, which may be related to the weak production of the virus-specific IgG and IgM. Recurrence of positive SARS-CoV-2 RNA could occur in mild COVID-19 possibly due to intermittent virus shedding, so strict quarantine and health surveillance should be taken to all the discharged COVID-19 patients to prevent the potential virus spread.